Ikigai: Filosofi Hidup Bahagia Orang Jepang - Muhamad Irfan (Literaksi: Jurnal Manajemen Pendidikan, 2023)
The purpose of this study was to find out the perspective of Muhamad Irfan Triyadi in learning about "Ikigai: Japanese Philosophy of Life" from the "1 Day of Success" youtube channel entitled "Ikigai". In this research study, researchers used a descriptive method, namely a method that was carried out by observing and noting techniques because the source of information was taken by listening to oral narratives. Ikigai comes from Japanese, 'Iki' means life, and 'Gai' means value. So in a sense, Ikigai is a concept that explains the meaning of life and happiness. The concept of Ikigai is a life value that comes from the habits of the Japanese people. With this concept, Japanese people are more enthusiastic about carrying out all their activities, as evidenced by the discipline and high Japanese work culture. Ikigai can make a person more meaningful, valuable, and balanced in life. So that this concept can be learned and implemented in daily activities.